2003
DOI: 10.1034/j.1600-0722.2003.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of healthy and inflamed human dental pulp to reduce hydrogen peroxide

Abstract: This study examined the defensive ability of human dental pulp against H2O2 in healthy and reversible and irreversible pulpitis tissues through determination of catalase activity by spectrophotometric methods. Thirty-five systemically healthy patients were donors of the pulp tissue, and pulp conditions were assessed using clinical and X-ray evaluations. Catalase activity was 1.61 +/- 0.23 U mg(-1) protein in the healthy tissues, 2.99 +/- 0.45 U mg(-1) protein in the reversible pulpitis tissues, and 2.44 +/- 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…Further, because the data on peroxide diffusion and cytotoxicity only refer to the last application of the product, it was not possible to assess the cumulative effect of the sessions, in which the bleaching procedure may have been more aggressive. In addition, several factors such as intrapulpal pressure, the presence of cytoplasmic prolongations in dentinal tubules [38,39], antioxidant enzymes, and the defense mechanisms of the pulp [40] could decrease the diffusion of peroxide as well mitigate the intensity of the aggression. Although physiological mechanisms exist that make it difficult for HP and its by-products to diffuse through the enamel and dentin and reach the pulp, in an in vivo study, de Souza Costa et al [7] observed an intense inflammatory reaction associated with areas of coagulation necrosis in the coronal pulp tissue of human mandibular incisors subjected to 38 % HP applied by the 30-min technique, which is similar to the techniques evaluated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Further, because the data on peroxide diffusion and cytotoxicity only refer to the last application of the product, it was not possible to assess the cumulative effect of the sessions, in which the bleaching procedure may have been more aggressive. In addition, several factors such as intrapulpal pressure, the presence of cytoplasmic prolongations in dentinal tubules [38,39], antioxidant enzymes, and the defense mechanisms of the pulp [40] could decrease the diffusion of peroxide as well mitigate the intensity of the aggression. Although physiological mechanisms exist that make it difficult for HP and its by-products to diffuse through the enamel and dentin and reach the pulp, in an in vivo study, de Souza Costa et al [7] observed an intense inflammatory reaction associated with areas of coagulation necrosis in the coronal pulp tissue of human mandibular incisors subjected to 38 % HP applied by the 30-min technique, which is similar to the techniques evaluated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the results of in vitro studies cannot be directly extrapolated to clinical situations (20). Vital teeth present a dentinal fluid flow produced by intrapulpal pressure, cytoplasmic processes of odontoblasts and other intratubular components, which may aid reducing bleaching gel diffusion through the dentinal tubules (6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dental pulp presents a lymphatic vessel system that participates in the elimination of external products that reach this tissue by trans-dentinal diffusion. Furthermore, due to the oxidative stress generated by the presence of free radicals, the defense system of the pulp cells is activated, releasing several endogenous antioxidant agents, such as peroxidases and catalases, which promotes an enzymatic degradation of hydrogen peroxide to avoid excessive tissue damage (20).…”
Section: Discussionmentioning
confidence: 99%
“…This action probably releases several endogenous antioxidant agents, such as peroxidases and catalases, which promote an enzymatic degradation of H 2 O 2 to avoid excessive tissue damage. 34 As time goes by, the amount of these oxidants and inflammatory mediators are likely reduced and fewer nerve fibers are therefore excited. Under these circumstances, 2% potassium nitrate may be effective in reducing tooth pain.…”
Section: 16mentioning
confidence: 99%